Effects of high and low dose of cadmium chloride on male Reproductive system in mice - Qadori, Yasamin T.; Al-shaikh, Mahera N. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Cadmium is highly toxic and carcinogenic environmental contaminant exposure to cadmium has been reported to reduce male fertility and there are several hypotheses that suggest how reduced male fertility may result from incorporation of cadmium. The purpose of this study was to determined the role of testicular ascorbic acid level in cadmium mediated oxidative damage on mice testis. Objectives:To know the extent of toxicity of cadmium chloride and its adverse effects on male reproductive system in mice . Methods:Fifteen adult albino male mice were divided into three groups, group one control and two experimental groups (low dose and high dose ).the experimental groups were injected with single dose of (0.14mg/BW) cadmium chloride in low dose and with (0.28mg/BW) cadmium chloride in high dose group ,intraperitoneally (ip) . The control group has given normal saline (0.9%) only .Animals were sacrificed after 15 days.The epididiymal sperm count, sperm abnormalities, tissue level of lipid peroxidation and testicular ascorbic acid level were estimated. Results:Exposure of mice to different doses of cadmium showed a decrease in the testicular weight (0.219±0.03), sperm count (124.6±0.2), ascorbic acid level (0.023±0.04), and increase in the testicular level of lipid peroxidation (0.49±0.1) and in the incidence of abnormal sperms. Exposure to high dose of cadmium showed a significant decrease in testicular weight (0.140±0.03), sperm count, (83.8±0.5) and increase in lipid peroxidation (0.79±2.1) compared to low dose group. Ascorbic acid level decreased significantly in high dose group compared to low dose group. Conclusion: Therefore the present study suggests that cadmium has deleterious effect on spermatogenesis and one of the possible mechanism in cadmium induced oxidative damage on mice testis cell might be mediated through its effect on reducing ascorbic acid level.